(untitled) (International Journal of Engineering and Computer Science, 2015)
: This is an Android based Smartphone Application for mobile payments or electronic wallet services. This work includes the mobile payment device and the paying client. This two device featuring 3 factor authentication and ad hoc network makes the transaction more secure as compared to the traditional credit card payment. The 3 factor authentication feature includes the IMEI(International Mobile Equipment Identity) authentication, facial bio-metric authentication and user authentication. The facial bio metric authentication is used to authenticate the user so that the unauthorized person should not be able to perform the transaction.